A novel replicon occurring naturally in Escherichia coli is a phage-plasmid hybrid. - Seufert, W (1988)
A novel DNA replicon in Escherichia coli was identified. It is the smallest natural isolate (1282 bp) found so far. In the presence of phage M13 it grows as a filamentous single-stranded DNA phage. Contrary to previously identified mini-phages this replicon displays sequence homology only to parts of the M13 viral and complementary strand origin. In the absence of M13 this DNA replicates autonomously. The only gene (arp) of the replicon encodes a 32-kd protein, which is essential for autonomous replication. The host rep gene required for replication of single-stranded DNA phages is dispensable. Distinct replication mechanisms are thus involved during growth as defective phage or as autonomous plasmid.